2020
DOI: 10.1038/s41433-020-01243-w
|View full text |Cite
|
Sign up to set email alerts
|

Near vision impairment among the elderly in residential care—the Hyderabad Ocular Morbidity in Elderly Study (HOMES)

Abstract: Background/objective To report on the prevalence and risk factors for near vision impairment (NVI) among the elderly in residential care in Telangana State in India. Methods Individuals aged ≥60 years were recruited from 41 'home for the aged' centres in Hyderabad, India. All participants had complete eye examinations including presenting and best-corrected visual acuity assessment for distance and near. NVI was defined as binocular presenting near vision worse than N8 (6/15) among those who had a normal prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…There was a significant correlation between education level and UNVA (18). With improvement in education level, the mean UNVA of participants gradually increased.…”
Section: Discussionmentioning
confidence: 82%
“…There was a significant correlation between education level and UNVA (18). With improvement in education level, the mean UNVA of participants gradually increased.…”
Section: Discussionmentioning
confidence: 82%
“…[ 5 ] also reported a higher prevalence in Andhra Pradesh and Telangana. [ 9 20 21 22 ] The higher prevalence in these studies might be due to inclusion of age group more than 40 years where the prevalence is expected to be higher. Also, the higher prevalence was noted in the weaving community due to the nature of work they are involved in.…”
Section: Discussionmentioning
confidence: 95%
“…Earlier papers reported that reading was the most important leisure activity in this cohort. [ 11 ] Higher education could be a surrogate indicator of better socio-economic status and hence increased access and affordability for seeking services and spectacles. This is further corroborated by higher odds for spectacles use among those in private homes compared to those in subsidized and free homes, though this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier publications, a high prevalence of correctable vision impairment for distance and near vision, even among those who were using spectacles, was reported. [ 10 11 ] This suggests that a more frequent change of spectacles is required in this age group. The present study reported that over 70% of the elderly had spectacles that were procured more than a year ago.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation